Emotional responses and coping strategies in adult Mexican population during the first lockdown of the COVID-19 pandemic: An exploratory study by sex - Luciana Ramos-Lira (Salud Mental, 2020)
Introduction The COVID-19 outbreak has involved a permanent and significant increase of fear and worries related to the virus and the measures taken to avoid contagion, such as confinement.Objective To explore the relationship between emotional responses and coping strategies used to face the first confinement among the Mexican adult population and inquire about differences by sex.Method An exploratory study was conducted through a self-administered online survey. It included questions about sociodemographic characteristics, emotions about pandemic information, and coping strategies. An informed consent form was presented prior to data collection. Chi square and Kruskal-Wallis were performed for bivariate analyses.Results A total of 2,650 participants completed the survey (21.6% were men). Significantly more men than women reported feeling calm (p < .001), hopeful (p = .011), and indifferent (p = .002). In contrast, more women, compared to men significantly reported feeling worried (p < .001), fearful (p < 0.001), and sad (p < .001). More women reported being emotionally close to other people (p = .027), seeking help from friends and family to share emotions and concerns (p < .001), and they frequently prayed as a coping strategy regardless of their emotions (p = .005).Discussion and conclusion While women are the least affected by the contagion and their symptoms are milder than in men, they present the most negative emotions, particularly of worry, but they also used more caring and helpful behaviors in comparison with men. These results can serve as a basis for developing research with a gender perspective that delves into the differences by sex found in this study.